Analysis of cleft palate cases - Nataraja NP; Sharma AK (Journal of All India Institute of Speech and Hearing, 1970)
This paper is intended just to report the problems seen in palate and lip cases who had reported to our Institute. The information given in this paper is collected from the case histories. All cases of cleft lip and palate here undergo E.N.T., Audiological, Speech and Psychological examinations, after giving a detailed case history. If necessary, the cases also are referred to the paediatrician or physician for further examinations.